Vacuum Hermetic Fumigation: A review. (March 2017) - Kumar, Sunil; Mohapatra, Debabandya; Kotwaliwale, Nachiket; Singh, Krishna Kumar
Abstract: Methyl Bromide and Phosphine are the most widely used chemical fumigants for insect control in stored grains. Ozone depletion, insect resistance, and residues on grain surface are the problems with the use of chemical fumigants. Zero tolerance for chemical residues under the international trade agreements require alternative solutions for safe and durable storage. Controlled atmosphere (CA)/modified atmosphere storage (MAS), temperature manipulation, hermetic storage, pressure manipulation (hyperbaric and hypobaric), safe fumigants of botanical derivatives and combination of these technologies have been practiced. Each method had certain merits and limitations restricting direct replacement for the existing chemical methods. This review explores chemical disinfection and physical methods with special emphasis on vacuum hermetic fumigation (VH-F). Modern hermetic storage systems utilize ultra-low oxygen and water permeability materials for storage of grains. Depletion of oxygen in the storage systems naturally or through the application of negative pressure (50–100 mm Hg) causes slower metabolic rate and finally cessation of basic metabolism and death of insects in a few days (up to 7 days). The efficacy of VH-F on the lethality of insects depends on vacuum level, stage and type of insects, temperature, CO2 level and exposure time. Suitability of vacuum hermetic storage systems for various agricultural produces as an alternative to chemical fumigation and the future scope of vacuum hermetic fumigation system are discussed.